Unmet needs in occupational health: prevention and management of viral hepatitis in healthcare workers in Ho Chi Minh City, Vietnam: a mixed-methods study - Tran Nguyen; Robert Gish; Binh T Nguyen; Amy Trang; Trang Pham; Hong K Tang; Loc Phan; Gary Mize; William M Lee; Anh Le; Hai T Phan; Doan Y Dao (BMJ Open)
Objectives Vietnam is an endemic area for hepatitis B virus and hepatitis C virus infection (HBV-HCV), yet its largest city, Ho Chi Minh City (HCMC), has no comprehensive policy to educate, screen, treat and protect healthcare workers (HCWs) from viral hepatitis. We conducted a mixed-methods study to document HBV-HCV infection rates, risk factors, local barriers and opportunities for providing education, screening and medical care for HCWs.Design This mixed-methods study involved an HBV and HCV serological evaluation, knowledge, attitude and practice survey about viral hepatitis and many in-depth interviews. Descriptive statistics and thematic content analysis using inductive and deductive approaches were used.Setting HCMC, Vietnam.Participants HCWs at risk of viral hepatitis exposure at three hospitals in HCMC.Results Of the 210 invited HCWs, 203 were enrolled. Of the 203 HCWs enrolled, 20 were hepatitis B surface antigen-positive, 1 was anti-hepatitis C antibody (anti-HCV Ab)-positive, 57 were anti-hepatitis B core Ab-positive and 152 had adequate anti-hepatitis B surface Ab (anti-HBs Ab) titre (≥10IU/mL). Only 50% of the infected HCWs reported always using gloves during a clinical activity involving handling of blood or bodily fluid. Approximately 50% of HCWs were still not vaccinated against HBV following 1 year of employment. In-depth interviews revealed two major concerns for most interviewees: the need for financial support for HBV-HCV screening and treatment in HCWs and the need for specific HBV-HCV guidelines to be independently developed.Conclusions The high HBV infection rate in HCWs coupled with inadequate preventive occupational practices among the population in HCMC highlight the urgent needs to establish formal policy and rigorous education, screening, vaccination and treatment programmes to protect HCWs from HBV acquisition or to manage those living with chronic HBV in Vietnam.